The effect of tricyclic antidepressant drugs on the uptake and metabolism of serotonin by the pineal gland in organ culture - Pillay, Manoranjenni (Rhodes University, Faculty of Pharmacy, Pharmacy, 1983)
The effect of tricyclic antidepressants (TADs) on a variety of pineal functions was assessed. TADs affected the uptake of Â³H-5HT into bovine pineal slices within a particular concentration range of these drugs, DESI, CLOMI and IMI appeared to inhibit uptake slightly, within a limited concentration range. Surprisingly, DESI appeared to be a relatively potent 5HT uptake inhibitor. The 5-HT re-uptake system in the pineal probably differes from that in brain tissue. TADs had a marked effect on the metabolism of Â³H-5HT in the rat pineal, in an organ culture system, MEL and N-acetylserotonin synthesis increased for the first 11 days and thereafter a slight decrease was observed. HTOH and HIAA also showed an initial increase followed by a slight decrease in synthesis. The synthesis of MTOH and MIAA was decreased. The possibility that TADs could affect HIOMT and SNAT synthesis and thereby change the metabolic pattern of 5-HT was investigated. TADs appeared to stimulate SNAT initially and thereafter a slight decrease from peak activity was observed. This is probably due to stimulation followed by development of subsensitivity of Î²-receptors, HIOMT activity also appeared to be affected by TADs. The existence of two types of HIOMT is suggested. There is a possibility that these changes in the metabolism of 5-HT could be implicated in the mechanism of action of TADs.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Antidepressants; Pineal gland -- Metabolsim; Serotonin